Tales of the ex-apes : how we think about human evolution - Marks, Jonathan M. 1955- (Univ. of California Press, 2015)
"This book is about the irreducibility of human evolution to purely biological properties and processes, for human evolution has incorporated the emergence of social relations and cultural histories that are unprecedented in the apes. Human evolution over the last few million years has involved the transformation from biological evolution into biocultural evolution. For several million years, human intelligence, dexterity, and technology all co-evolved with one another, although the first two are organic properties and the last is inorganic. Over the last few tens of thousands of years, the development of new social roles - notably, spouse, father, in-laws, and grandparents - have been combined with new technologies and symbolic meanings to produce the familiar human species. This leads to a fundamental evolutionary understanding of humans as biocultural ex-apes; reducible neither to an imaginary cultureless biological core, nor to our ancestry as apes. Consequently, there can be no 'natural history' of the human condition, or the human organism, which is not a 'natural/cultural history'."...Provided by publisher